1992
DOI: 10.1093/oxfordjournals.humrep.a137750
|View full text |Cite
|
Sign up to set email alerts
|

The influence of slow and ultra-rapid freezing on the organization of the meiotic spindle of the mouse oocyte

Abstract: We have investigated the effect of ultra-rapid versus slow freezing on the meiotic spindle of the mouse oocyte. A slow freezing protocol [1.5 M dimethyl sulphoxide (DMSO)] and an ultra-rapid protocol (3.5 M DMSO/0.5 M sucrose) have been compared. Oocytes were fixed at different time points as follows: after prefreeze equilibration, immediately after thawing and after 60 or 180 min of post-thaw recuperation. The spindle was visualized with a monoclonal anti-alpha-tubulin antibody followed by an immunogold-silve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
39
0
2

Year Published

1995
1995
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 0 publications
1
39
0
2
Order By: Relevance
“…This allowed assessment of the correlation between mitochondrial distribution and embryo developmental competence. Previous studies of vitrification in mouse oocytes have shown that incubation for 2 or 3 hrs resulted in a higher incidence of normal spindles than incubation for 1 hr, and that fertilization and blastocyst formation of vitrified mouse oocytes inseminated after 1 hr of incubation were significantly lower than for control specimens, but increased with insemination after incubation for 2 or 3 hrs (Aigner et al 1992;Chen et al 2001Chen et al , 2003. Therefore, activation of oocytes was observed after incubation for 30 min following vitrification and thawing.…”
Section: Discussionmentioning
confidence: 85%
“…This allowed assessment of the correlation between mitochondrial distribution and embryo developmental competence. Previous studies of vitrification in mouse oocytes have shown that incubation for 2 or 3 hrs resulted in a higher incidence of normal spindles than incubation for 1 hr, and that fertilization and blastocyst formation of vitrified mouse oocytes inseminated after 1 hr of incubation were significantly lower than for control specimens, but increased with insemination after incubation for 2 or 3 hrs (Aigner et al 1992;Chen et al 2001Chen et al , 2003. Therefore, activation of oocytes was observed after incubation for 30 min following vitrification and thawing.…”
Section: Discussionmentioning
confidence: 85%
“…It has been reported in murine [42] and bovine [43] oocytes that the abnormal appearance of the spindle following the slow freezing and rapid thawing returned to be normal after a period of incubation. It has been reported that, in the context of slow freezing, a pre-incubation of 2 h was required for the oocytes before insemination to im prove the fertilizability and embryonic development of the freezing-thawed oocytes [41,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Incubation of frozen-thawed oocytes before insemination seems to allow recovery from the injury associated with the slow freezing procedure [42,43]. Pre-incubation of post-thawed bovine oocytes improves the fertilizability and embryonic developmental capacity [44,45].…”
mentioning
confidence: 99%
“…Damage of microtubles and microfilaments has been thought to be the major cause of loss or decrease of viability of oocytes after cryopreservation [35][36][37]. Cryo-injury to these elements is affected by the cryopreservation methods and cryoprotective agents used [35][36][37].…”
Section: Discussionmentioning
confidence: 99%